Ending Preventable Child Deaths from Pneumonia and Diarrhoea in Afghanistan: An Analysis of Intervention Coverage Scenarios Using the Lives Saved Tool - Ariel Higgins-Steele; Khaksar Yousufi; Sharmina Sultana; Alawi Sayed Ali; Sherin Varkey (Journal of Tropical Medicine)
Background. Despite improvements in child health, Afghanistan still has a heavy burden of deaths due to preventable causes: 17% of under-5 deaths are due to pneumonia and 12% are due to diarrhoea. Objective. This article describes the situation of childhood pneumonia and diarrhoea in Afghanistan, including efforts to prevent, protect, and treat the two diseases. It estimates lives saved by scaling up interventions. Methods. A secondary analysis of data was conducted and future scenarios were modelled to estimate lives saved by scaling up a package of interventions. Results. The analysis reveals that 10,795 additional child deaths could be averted with a moderate scale-up of interventions, decreasing the under-five mortality rate in Afghanistan from 55 per 1,000 live births in 2015 to 40 per 1,000 in 2020. In an ambitious scale-up scenario, an additional 15,096 lives could be saved. There would be a 71% reduction in child deaths due to these two causes between 2016 and 2020 in the ambitious scenario compared to 47% reduction in the moderate scenario. Conclusion. Significant reductions in child mortality can be achieved through scale-up of essential interventions to prevent and treat pneumonia and diarrhoea. Strengthened primary health care functions and multisector collaboration on child health are suggested.